Impact of Psychological Resilience on Bullying Prevention: An Empirical Study in Amman Private Schools - Hussein Khazer Almajali; Eman Saeed Al-Bourini; Nisreen Al-Shamaileh; Areen A.Q Bajes Almajali (Migration Letters, 2023)
This research delves into the pivotal role of psychological resilience, encompassing characteristics of tenacity, strength, and optimism, in the context of bullying prevention within private schools in Amman. Employing a cross-sectional research design, data for the research were gathered through a self-administered questionnaire distributed to psychological counsellors. The final research sample comprised 242 responses, representing a percentage of 75.6% of the total questionnaires distributed. The data underwent processing, and the research hypotheses were scrutinized via structural equation modeling. The findings underscore the positive contribution of psychological flexibility to the enhancement of bullying prevention. Results exhibiting high levels of psychological flexibility, characterized by their ability to persist in the face of challenges, emotional strength, and a positive outlook, significantly contributed to the prevention of bullying behaviours. Consequently, a series of recommendations were proposed, with a primary emphasis on the development and implementation of comprehensive resilience-building programs seamlessly integrated into school curricula. These programs should be meticulously designed to systematically impart crucial skills related to psychological resilience, equipping students with the tools necessary to effectively navigate and prevent bullying incidents. The research also identified a set of limitations and pointed towards future research directions.